Information Communication Technology Platforms as a Predictor of Scholastic Adjustment among Undergraduates in Rivers State (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigates Information Communication Technology platforms as a predictor of scholastic adjustment among undergraduates in Rivers State. Three research questions and three corresponding null hypotheses were used to guide the study. The study adopted correlation research design. The total population of the study comprised all 14000 undergraduates in Rivers State owned universities. A sample of 500 undergraduates were drawn from the population using multi-stage sampling procedure. One self-structured instrument titled "information Communication Technology Platform and Scholastic Adjustment Predictor Scale (ISAPS) was used for data collection. The reliability of the instrument was done using Cronbach Alpha method. The ISAPS yielded a coefficient of .78. Three experts; one in guidance and counselling and two others in measurement and evaluation validated the instrument via face and content validity. The instrument were administered by the researcher and two research assistants and was retrieved at the spot. Simple linear regression analysis method was used to answer the research questions and test the null hypotheses at 0.05 alpha level of significance. The findings of the study showed that information communication platforms significantly predicted students’ scholastic adjustment among undergraduates in Rivers State. In line with the findings of the study the researcher’s recommendations were made.